Analisis Kepuasan Pelanggan Dengan Menggunakan Komparasi Fuzzy Inference System Metode Sugeno Dan Tsukamoto Pada Hotel Kristal Jakarta - Sehan, Achmad (Scientia Sacra: Jurnal Sains, Teknologi dan Masyarakat, 2022)
Customer satisfaction is the most important part which is influenced by several factors, such as: quality of service, price, atmosphere & product. Customer satisfaction encourages customers to commit to a company’s products and services so that it has an impact on increasing sales of a product. The problem taken from this research is that in the last 2 years from 2019-2020 the number of consumers at Kristal Hotel has decreased. The purpose of this research is to find out how big the level of customer satisfaction with the services of Hotel Kristal by comparing the two Fuzzy Inference System methods, the Sugeno method and the Tsukamoto method. There are five attributes that will be used, namely service quality, product quality, price quality and atmosphere quality as input attributes, while the output attribute is customer satisfaction. The level of customer satisfaction itself is not satisfied, less satisfied, quite satisfied, satisfied and very satisfied. The research data was sampled by distributing questionnaires to 100 consumer respondents at Crystal Hotel at random. In this study, a comparative analysis of the results of the Sugeno method and the Tsukamoto method was carried out by testing using MAPE with the MATLAB toolbox to determine the most accurate method in determining customer satisfaction from Hotel Kristal. So that the Management can take steps which sectors need to be improved so that Crystal Hotel again gets more consumers.